The Effect Of Full Court Skill And Drill Training On Basketball Players Shooting Accuracy Under Fatigue Conditions - M. Farlyzzahaby Deska Utama; Dadang Warta Chandra Kesuma; Lalu Hulfian (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Basketball shooting performance frequently declines under fatigue conditions, yet evidence regarding training approaches specifically designed to improve shooting accuracy in fatigue-related situations remains limited. While previous studies have examined the acute effects of fatigue on shooting performance, fewer studies have investigated training interventions that repeatedly expose players to game-like fatigue during shooting execution. This study aimed to determine the effect of full court skill and drill training on basketball players’ shooting accuracy under fatigue conditions. The study used a pre-experimental one-group pretest–posttest design involving 15 players from Momentum Basketball Club selected through total sampling. The intervention was conducted for three weeks with a frequency of three sessions per week. Each session integrated dribbling, passing, transition movement, sprinting, and shooting drills across the full court to simulate game-like fatigue. Shooting accuracy was measured before and after the intervention using a shooting test performed after an intensive activity protocol. Data were analyzed using IBM SPSS Statistics through descriptive statistics, the Shapiro–Wilk normality test, paired-samples t-test, Wilcoxon signed-rank test, 95% confidence interval estimation, and Cohen’s dz effect size. The results showed that the mean pretest score increased from 3.33 to 6.67 in the posttest, with a mean gain of 3.33 points. The paired-samples t-test indicated a significant improvement, t(14) = 20.92, p < 0.001, with a very large effect size (Cohen’s dz = 5.40). The Wilcoxon signed-rank test confirmed the same conclusion, W = 0.00, p < 0.001. These findings indicate that full court skill and drill training is effective for improving shooting accuracy when players perform under fatigue. The study contributes practically to the design of basketball training programs that combine technical execution, physical load, and match-specific pressure